Reducing Cadmium Accumulation in Plants: Structure–Function Relations and Tissue-Specific Operation of Transporters in the Spotlight - Huang, Xin; Duan, Songpo; Wu, Qi; Yu, Min; Shabala, Sergey (Plants (Basel), 2020)
Cadmium (Cd) is present in many soils and, when entering the food chain, represents a major health threat to humans. Reducing Cd accumulation in plants is complicated by the fact that most known Cd transporters also operate in the transport of essential nutrients such as Zn, Fe, Mn, or Cu. This work summarizes the current knowledge of mechanisms mediating Cd uptake, radial transport, and translocation within the plant. It is concluded that real progress in the field may be only achieved if the transport of Cd and the above beneficial micronutrients is uncoupled, and we discuss the possible ways of achieving this goal. Accordingly, we suggest that the major focus of research in the field should be on the structure–function relations of various transporter isoforms and the functional assessment of their tissue-specific operation. Of specific importance are two tissues. The first one is a xylem parenchyma in plant roots; a major “controller” of Cd loading into the xylem and its transport to the shoot. The second one is a phloem tissue that operates in the last step of a metal transport. Another promising and currently underexplored avenue is to understand the role of non-selective cation channels in Cd uptake and reveal mechanisms of their regulation.